Penamaan Bunyi Segmental dan Suprasegmental Pada Pedagang Keliling - Wahyu Oktavia (Jurnal Bahasa Lingua Scientia, 2018)
The study, titled "The Naming of Segmental and Suprasegmental Sound to Mobile Traders" aims to describe the forms of naming the segmental and suprasegmental sounds used by the traveling traders. The type of research used is descriptive qualitative method whose data have been obtained, classified, classified, interpreted and then analyzed to obtain the data being studied. The results of this study indicate that there is uniqueness that is spoken between fellow traders located at the sound level.